Islamic Sharia-based Group Microlending Initiative and Implementation Trajectory Experience in Afghanistan (Global Journal of Management and Business Research, 2013)
Although some people think the concept of Sharia Law Islamic Banking system is ancient, modernized Islamic Banking has been operating for many decades around the world. Countries such as Bangladesh, Malaysia, UK, Singapore, Pakistan and Bahrain competitively run their Islamic banking side by side with modern commercial banks that are successful in their banking operations and are financially sustainable. However, Islamic Sharia micro financing services are new and rare in the Muslim world although these services can easily help marginalized people to become economic actors in the society and to address the issue of poverty.
Keywords: grameen bank; ijara; islamic sharia based financing and banking; mudaraba; murabaha; islamic sharia based microfinancing; and unhcr